Selective magnetic resonance imaging of magnetic nanoparticles by acoustically induced rotary saturation. Issue 1 (23rd December 2014) - Zhu, Bo; Witzel, Thomas; Jiang, Shan; Huang, Susie Y.; Rosen, Bruce R.; Wald, Lawrence L.
Abstract : Purpose: The goal of this study was to introduce a new method to selectively detect iron oxide contrast agents using an acoustic wave to perturb the spin‐locked water signal in the vicinity of the magnetic particles. The acoustic drive can be modulated externally to turn the effect on and off, allowing sensitive and quantitative statistical comparison and removal of confounding image background variations. Methods: We demonstrated the effect in spin‐locking experiments using piezoelectric actuators to generate vibrational displacements of iron oxide samples. We observed a resonant behavior of the signal changes with respect to the acoustic frequency where iron oxide is present. We characterized the effect as a function of actuator displacement and contrast agent concentration. Results: The resonant effect allowed us to generate block‐design "modulation response maps" indicating the contrast agent's location, as well as positive contrast images with suppressed background signal. We found that the acoustically induced rotary saturation (AIRS) effect stayed approximately constant across acoustic frequency and behaved monotonically over actuator displacement and contrast agent concentration. Conclusion: AIRS is a promising method capable of using acoustic vibrations to modulate the contrast from iron oxide nanoparticles and thus perform selective detection of the contrast agents, potentially enabling more accurate visualization of contrast agents in clinical and research settings. Magn Reson Med 75:97–106, 2016. © 2015 Wiley Periodicals, Inc.